Diversity and abundance of epiphytic bromeliads in “El Punto ” Santa Catarina Ixtepeji, Oaxaca - Carvente-Acteopan, Sabina; Pérez Olvera, Ma. Antonia; Flores-Cruz, María; Navarro-Garza, Hermilio; Flores-Hernández, Noé (Revista Mexicana de Ciencias Agrícolas, 2017)
Bromeliads are plants that grow in forests and jungles of the American continent. In Mexico the reported bromeliads surpass 363 and Oaxaca has 189 of them. The municipality of Ixtepeji and its agencies including “El Punto” in Oaxaca, take advantage of epiphytic bromeliads. Since 2008 they have a UMA, where their members collect in specific areas. In order to determine the diversity and abundance of bromeliads as ecological indicators of forest management, a targeted sampling was carried out during 2015 in four bromeliad utilization areas: La Cruz de Yovaneli, La Curva de San Miguel, Reynoso and La Petenera. 300 trees were selected in each zone of which 87 are oak ( Quercus sp.), 32 pine ( Pinus sp.) and one Bursera sp tree. In the forophytes, bromeliad species were quantified. Most bromeliads diversity and abundance of species was observed in Tillandsia (11 sp.) genus, with specificity location of at least two species per area. The oak was the forophyte that showed the greatest diversity and abundance of bromeliads. The Shannon diversity index was average in the Curva de San Miguel and Reynoso areas (1.5 and 1.3) and low for La Cruz de Yovaneli and La Petenera areas (0.6 and 0.4).